(untitled) (Global Journal of Science Frontier Research, 2012)
In the last three decades, Nigeria had been confronted with the problem of how to attain balanced and even development. Attempts at resolving this problem had brought about the raging issue of how to evolve an acceptable formula for allocating available resources amongst the various geo-political units. Efforts aimed at evolving such workable arrangements are being hampered by inadequate information on the amount, location and distribution of these resources. Consequently, the problem continues to recur in every facet of national life and have since remained intractable. Against this backdrop, this paper examines crucial issues surrounding the Nigerian resource question, the potentials of cartography and geographic information system (GIS) in resolving these issues particularly as it relates to resource mapping in Nigeria. It goes further to address the place of cartography and GIS as viable instruments of spatial engineering aimed at ensuring balanced development through effective resource allocation in a developing society like Nigeria.